A greener way to stay: The role of perceived sustainability in generating loyalty to Airbnb - Brian Garrod (International Journal of Hospitality Management, 2023)
The sustainability potential of peer-to-peer (P2P) accommodation sharing will not be fully achieved until sustainability is fully understood as a motivating force. This study examines the influence of perceived sustainability and familiarity on loyalty intentions with platform trust and satisfaction as mediators and age as a moderator. An online survey with 507 UK Airbnb users found that perceived sustainability and familiarity are effective drivers of consumers’ loyalty in relation to Airbnb, alongside the mediators of platform trust and satisfaction. In addition, the effect of perceived sustainability on platform trust is greater among younger users, which feeds further to satisfaction and consequently loyalty. This timely study adopts an integrative approach which recognises the interplay of sustainability, familiarity, trust and satisfaction in predicting loyalty intentions for P2P accommodation. This can, in turn, help to unlock the potential of P2P accommodation to deliver more sustainable outcomes for people, places and the planet.